Outcome of archival management in the Archives System of the Catholic religious congregation of Priests of the Blessed Sacrament in Spain. - Yamir Toledo Díaz, Édison (Revista General de Información y Documentación, 2016)
The article analyzes the main results obtained in the archival processing through the phases of identification, appraisal, organization and description of the documentary holdings of Congregation of the Blessed Sacrament in Spain, which consists of one Provincial Archives and four local archives. This study summarized that it is perfectly possible to apply the theoretical, methodological and practical basis of the Archival science in this kind of archival institutions.